Earthquake nation : the cultural politics of Japanese seismicity, 1868-1930 - Clancey, Gregory K. (University of California Press, 2006)
Reaching from the Meiji Restoration to the Great Kantō Earthquake of 1923, Clancy's innovative study not only moves earthquakes nearer to the centre of modern Japanese history but also shows how fundamentally Japan shaped the global art science, and culture of natural disaster.